2013
DOI: 10.1007/s12013-013-9611-y
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Monitoring of Small Intestinal Oxygen in a Rat Model of Chronic Mesenteric Ischemia

Abstract: We noninvasively monitored the partial pressure of oxygen (pO2) in rat small intestine using a model of chronic mesenteric ischemia by electron paramagnetic resonance oximetry (EPR) over a 7-day period. The particulate probe lithium octa-n-butoxynaphthalocyanine (LiNc-BuO) was embedded into the oxygen permeable material polydimethyl siloxane (PDMS) by cast-molding and polymerization (Oxy-Chip). A one-time surgical procedure was performed to place the Oxy-Chip on the outer wall of the small intestine (SI). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…A non-invasive method of determining tissue pO 2 by electron paramagnetic resonance (EPR) oximetry showed oxygen levels of less than 2% in the intestinal lumen, 8% in the small intestinal wall, and 3 % at the villus tip [105]. These conditions of physiological oxygenation were termed physioxia.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A non-invasive method of determining tissue pO 2 by electron paramagnetic resonance (EPR) oximetry showed oxygen levels of less than 2% in the intestinal lumen, 8% in the small intestinal wall, and 3 % at the villus tip [105]. These conditions of physiological oxygenation were termed physioxia.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It has been shown that the pericellular oxygen concentration of Caco-2 cells cultured in ambient incubator conditions (18-21% oxygen) can drop to 16% oxygen when cells are cultured on membrane inserts 18 . This high level of oxygenation observed under standard incubator conditions serves as a significant confounding factor when considering that in vivo oxygen levels range from 1%-11% oxygen 13,19 . Additionally, altered gene-expression and phenotypes have been observed when comparing aerobic cultures to cultures grown at physiologic levels of oxygen, suggesting that ambient oxygen induces hyperoxic, potentially atypical, phenotypes in cell culture 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Gardner [40,41] already discussed upon this topic, but there is still limited evidence that larger peptides and protein are taken up intactly by the intestine [42,43]. From the existence of food allergies, however, it can be deduced that indeed a small amount of immunologically active food protein can be taken up and enter the circulation [44]. In this thesis, I will examine whether this also applies for several specifically chosen dietary proteins and peptides and whether a physiological challenge, in this case exercise, can affect this uptake.…”
Section: Digestion and Absorption Of Dietary Proteinmentioning
confidence: 99%
“…Two important AAs in citrulline metabolism are glutamine and arginine, as a precursor and product of citrulline, respectively. Depletion of glutamine, which is the main fuel for enterocytes, results in plasma citrulline depletion [44,45]. Findings in mice suggest that during shortage of available glutamine, enterocytes possibly prioritize its utilization for energy over the production of citrulline [46].…”
Section: Intestinal Metabolic Capacitymentioning
confidence: 99%
See 1 more Smart Citation